Work Is for the People : a Treatise on the -Isms. - Burrell, Joseph (Algora Pub., 2011)
Work is for the People is for everyone who cares about civil rights, human rights, and the rights of working people and consumers as well as those who believe that government is not automatically evil and incompetent. The author reminds us that in a democracy, the system of work and the economy are supposed to be designed to benefit the people, not owners and bosses; he shows that corporatism is another name for fascism, and calls for a fairly-regulated capitalism in place of the travesty of the unelected, unregulated, and predatory capitalism we have now. Despite its strong language, this is.